AKTIVITAS PROMOSI TORAJA DESTINATION MANAGEMENT ORGANIZATION (DMO) DALAM MEMPROMOSIKAN OBJEK WISATA DI TORAJA - Sri Nur Rahmi; Kahar Kahar; Sudirman Karnay (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2016)
The purpose of this study was to determine the promotional activities and the factors that affect Toraja Destination Management Organization (DMO) in promoting the attractions in Toraja. This study uses qualitative descriptive analysis. Data collection methods used were interviews, observation and documentation. The results showed that the Toraja Destination Management Organization (DMO) can not be separated from the promotion mix. The five forms of promotion mix, not all do. Forms of promotion mix done of personal selling, advertising, public relations, and direct marketing, while the use of a variety of intensive not do. Additionally, Toraja Destination Management Organization (DMO) has moved towards the process of Integrated Marketing Communications Integrated Marketing Communication or that include the coordination efforts of the various elements of promotional and other marketing activities. Meanwhile, a supporting factor comes from two aspects, internal and external, internal refers to the performance and creativity as well as measures of innovative Toraja Destination Management Organization (DMO), while factors external support in the form of support from other parties who deal directly in the world of tourism , While inhibiting factor is the gap between the readiness of tourism development with incessant promotion that has been done is not effective.